The EU Internal Market in the Next Decade - Quo Vadis? - Mifsud, Ivan,; Sammut, Ivan, (International Law E-Books Online, Collection 2025., 2025)
This essential collection of essays delves into the European Union's Internal Market, offering a thorough analysis inspired by the Council of the European Union's pivotal 2024 conclusions. The book outlines a strategic roadmap for the market's future development, making it a critical resource for academic libraries. In three parts, the volume examines (I) Citizens' Rights, highlighting the impact of EU regulations on individuals, (II) the challenges and opportunities posed by digital rights and Artificial Intelligence, crucial for the market's progression over the next decade, and (III) substantive rights, providing insights into legislative and policy measures vital for the market's evolution. Ideal for researchers, policymakers, and students, this book is an invaluable resource for understanding and influencing the future of the EU's economic landscape.